Framework in developing model of interfloor leakage in high-rise residential buildings in Malaysia - Siti Rosemawar Mohd Sahi,; Norngainy Mohd Tawil,; Wai, Kuan You (Penerbit Universiti Kebangsaan Malaysia, 2022)
Interfloor leakage is amongst the highest claims reported to the Strata Management Tribunal. This defect affects strata communities directly and indirectly in cost of repair, occupant safety, health and disputes. Regulation 55 of the Strata Management (Management and Maintenance) Regulation 2015 under Strata Management Act 2013 defines interfloor leakage as any evidence of dampness, moisture or water penetration, and has underlined the work process of interfloor inspection. However, issues are investigating the cause of leakage and repair costs, and determining who is responsible for the repair. Conducting defect assessment by standards is the collection of systematic information to evaluate building performance, investigate defect elements and recommend appropriate repairs. The research concept framework examines the effect or influence of each construct on another construct. Constructs are three, namely, interfloor leakage management, legislation and owner satisfaction. Based on the literature review, the conceptual framework is produced, and each of these constructs is developed with several dimensions to be tested. The sequential exploratory design method is used with a combined approach of qualitative interviews and discussions with experts in the field of property management and building pathology to form a questionnaire for distribution to the management. This research is essential to decide how to reduce disputes, discuss the costs of repair and select a party to execute repairs that create quality strata management that benefits the owners, management and stakeholders.